Gaussian Fibonacci Circulant Type Matrices - Zhaolin Jiang; Hongxia Xin; Fuliang Lu (Abstract and Applied Analysis)
Circulant matrices have become important tools in solving integrable system, Hamiltonian structure, and integral equations. In this paper, we prove that Gaussian Fibonacci circulant type matrices are invertible matrices for n>2 and give the explicit determinants and the inverse matrices. Furthermore, the upper bounds for the spread on Gaussian Fibonacci circulant and left circulant matrices are presented, respectively.